Beyond Solar Fuels: Renewable Energy‐Driven Chemistry. Issue 22 (9th November 2017) - Lanzafame, Paola; Abate, Salvatore; Ampelli, Claudio; Genovese, Chiara; Passalacqua, Rosalba; Centi, Gabriele; Perathoner, Siglinda
Abstract: The future feasibility of decarbonized industrial chemical production based on the substitution of fossil feedstocks (FFs) with renewable energy (RE) sources is discussed. Indeed, the use of FFs as an energy source has the greatest impact on the greenhouse gas emissions of chemical production. This future scenario is indicated as "solar‐driven" or "RE‐driven" chemistry. Its possible implementation requires to go beyond the concept of solar fuels, in particular to address two key aspects: i) the use of RE‐driven processes for the production of base raw materials, such as olefins, methanol, and ammonia, and ii) the development of novel RE‐driven routes that simultaneously realize process and energy intensification, particularly in the direction of a significant reduction of the number of the process steps. Abstract : I love low‐C :Renewable energy (RE)‐driven chemistry represents a possible revolution for a low‐carbon economy. Its possible implementation requires to go beyond the concept of solar fuels to address two key aspects: the use of RE‐driven processes for the production of base raw materials and the development of RE‐driven routes that simultaneously realize process and energy intensification.